Financial management of pension funds in Algeria -Case study of the National Pension Fund in Constantine- - Benlaharche, sarah (Journal of Research in Finance and Accounting, 2022)
This research aims to study the reality of the financial management of pension funds in Algeria; The National Pension Fund (CNR), the National Social Security Fund (CNAS and CASNOS), the Special Retirement Fund for Senior Officials of the State (FSR). In order to achieve the objectives of this research, the descriptive method was relied by describing the retirement system followed in Algeria, as well as the analytical method to analyze its reality, where the field study was conducted at the level of the National Pension Fund in Constantine State. This research reached a number of results, the most important of which is that the retirement system in Algeria is financed by the contributions of workers and employers, and the state also contributes significantly to the revenues of pension funds and is trying to cover the existing deficit due to the large increase in the number of retirees in recent years.